Effectiveness of a comprehensive rehabilitation service model on clinical outcomes in subacute stroke patients - Tantalanukul, Seubtrakul; Ekwatthanakun , Chitchanok (Health Science, Science and Technology Reviews, 2025)
This study aimed to develop and evaluate the effectiveness of a comprehensive rehabilitation service model for subacute stroke patients, covering inpatient, outpatient, and home-based care, led by a physiatrist. A randomized controlled trial was conducted at Uttaradit Hospital, Thailand, from January to December 2022. Seventy participants were randomized into intervention (n=35) and control (n=35) groups. The intervention group received the developed rehabilitation model, while the control group received standard care. Outcomes were assessed at 4, 12, and 24 weeks. Results showed that the intervention group had significantly better improvements in Barthel Index score (43.7±18.9 vs 25.9±17.6, p<0.001), Modified Rankin Scale score (-1.6±1.0 vs -1.0±0.9, p=0.012), and Stroke Specific Quality of Life Scale score (72.9±30.5 vs 41.5±28.6, p<0.001) at 24 weeks compared to the control group. Additionally, the intervention group demonstrated significantly greater improvements in depression (-5.7±3.5 vs -3.0±3.1, p=0.001) and walking ability (0.43±0.22 vs 0.21±0.18 m/s, p<0.001). In conclusion, the developed rehabilitation service model was effective in improving activities of daily living, reducing disability levels, and enhancing quality of life of subacute stroke patients. The distinctive features of this model include continuity of rehabilitation services and the integration of telerehabilitation for home-based care, which is particularly suitable for rural areas with limited resources.